Thorax Radiography Examination Procedure In Pneumonia With A Specific Process Of Pulmonary Tuberculosis In The Radiology Installation Of Semarang District Hospital - Utami, Lucky Restyanti Wahyu; Rosidah, Siti; Prayoga, Aryadiva Nugrahaning (Postgraduate Program , Poltekkes Kemenkes Semarang, 2024)
Pneumonia is inflammation or acute inflammation of the lung tissue caused by various microorganisms such as bacteria, viruses, parasites, fungi, exposure to chemicals or physical damage to the lungs. Meanwhile, pulmonary tuberculosis is caused by the bacterium Mycobacterium tuberculosis (M. tuberculosis) and is an infectious disease. The use of thorax radiography is one of the most common radiological examinations in diagnosing diseases in the area of the heart and lungs. Radiography of the lungs is necessary to confirm the diagnosis of pneumonia. The accuracy of the diagnosis of pulmonary tuberculosis depends on the method of taking examination material and the availability of diagnostic tools, for example microbiological tests, anatomical pathology, serology, thorax radiography and others. This study aims to find out how the thorax radiographic examination procedure is carried out in cases of pneumonia with a specific process of pulmonary tuberculosis in the Radiology Installation of Semarang District Hospital. This type of research is descriptive descriptive research with a case study approach. The research subjects used in this study were 1 patient who performed a thorax radiographic examination in a case of pneumonia with a specific process of pulmonary tuberculosis at the Radiology Installation of Semarang District Hospital. From the results of the data obtained, it is known that in the procedure for examining thorax radiography in cases of pneumonia with a specific process of pulmonary tuberculosis there is no special patient preparation, the patient is only asked to remove objects that can interfere with radiographic images in the area of the thoracic cavity being examined. The tools used include x-ray machines, bucky stands, imaging plates and computed radiography. The projection used is the postero anterior (PA) projection.